Evaluasi Sistem Informasi Pendaftaran Pasien Rawat Jalan Di Rumah Sakit X Kota Kediri - Reny Nugraheni; Yoanita Indra Kumalasari (Politeknik Negeri Jember, 2020)
Hospital information system is an arrangement with data collection, data processing, presentation of information, analysis and inferences of information, is plays a role in supporting quality control, productivity assessment, and program evaluation. X Hospital is one of the most favored hospitals by patients or visitors. Data on the number of visitors of patients for three consecutive years X Hospital highest hospital compared with other hospitals in the city of Kediri. The purpose of this study is to evaluate the implementation of outpatient registration information system information at X Hospital Kediri. Design of this study is quantitative descriptive. Data were collected through questionnaires and observations. The results showed that the information system of outpatient registration is not optimal because the outpatient registration process is not in accordance with the standard operating procedures established. Data completeness and accuracy are in good category. Patient satisfaction on outpatient service is also in good category